Pengaruh Pembelajaran Ekonomi Islam Terhadap Minat Mahasiswa Berinvestasi di Pasar Modal (Studi Kasus Mahasiswa FEBI UIN Raden Fatah Palembang) - Dea, Dea Tirta Kirana; Amiyati, Rara; Kurnia, Julisa (Asyafina Journal: Jurnal Akademi Pesantren, 2023)
Abstract This study aims to: (1) Determine the effect of learning Islamic economics on students' interest in investing in the capital market in FEBI students at UIN Raden Fatah Palembang. (2) Knowing the effect of investment motivation on interest in investing in the capital market in FEBI students at UIN Raden Fatah Palembang. (3) Knowing the effect of learning and investment motivation on students' interest in investing in the capital market in FEBI students at UIN Raden Fatah Palembang. This research uses a quantitative approach with an associative descriptive method. The population in this study were students of the Islamic Economics S1 Study Program, FEBI UIN Raden Fatah Palembang and had passed the Portfolio and Investment Theory course. The sample in this research is 100 students. Collecting data in this study using a questionnaire method. Based on the results of the significance test, it shows that there is a sig value of 0.026 <0.05, the results of this value indicate that "investment education has an effect on interest in investing in the capital market". The results of the significance test show that there is a sig value of 0.000 <0.05 from the results of this value indicating that "investment motivation has an effect on investment interest". The results of the Fcount test were 158,742 with sig Fcount <5% (0.000 <0.05), so it was concluded that "investment education and investment motivation simultaneously influence the interest in investing in the capital market in FEBI students at UIN Raden Fatah Palembang". The magnitude of the coefficient of determination (R2) is 0.766. This shows that the independent variables jointly affect the dependent variable by 76.6%, the remaining 20.4% is influenced by other variables. Keywords: Learning Islamic economics, interest in investing, capital markets